BRANDING STRATEGY IN MADRASAH BASED LOCAL KNOWLEDGE - Taufiq, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to determine how branding strategies in madrasas based on local wisdom are becoming increasingly relevant for identifying, developing and implementing strategic steps in promoting MTs. Zainul Irsyad and preserving local wisdom through extracurricular martial arts, Pencak Silat, Pagar Nusa. Likewise, social media has become a practical application to bridge information on superior programs implemented by educational institutions to the public as the main consumers in determining the right educational institution for their children . This research uses a qualitative method with a case study approach using interview, observation and documentation data collection techniques which are then analyzed through several steps of data collection, data reduction, data presentation and conclusions . Testing the validity of the data in this study used triangulation. The results of this research are that MTs Zainul Irsyad presents the extracurricular martial arts pencak silat Pagar Nusa as an advantage in shaping the character of students, encouraging community participation through school committees in extra-curricular activities based on local wisdom, promotion via Social Media by choosing the right communication platform, collaboration with Relevant Parties by involving local governments and other relevant actors so that this program can be sustainable and have a positive impact. The success of a branding strategy based on local wisdom through extra-curricular martial arts pencak silat Pagar Nusa can be measured through; (1) increasing students' knowledge about local wisdom, (2) their active participation in pencak silat martial arts activities at several events, and (3) a significant impact on the acceptance of new students in the next academic year